Penyusunan Hazard Identification Risk Assessment and Risk Control (HIRARC) Di PT. X - Irawan, Shandy; Panjaitan, Togar W.S; Bendatu, Liem Yenny (Jurnal Titra, 2015)
PT. X is a company which produces a variety of glassware product. PT. X wants to develop Hazard Identification Risk Assessment and Risk Control (HIRARC) in order to fulfill the requirement of OHSAS 18001:2007 application. The area covers in raw materials warehouse, production, and finished good warehouse.The preparation of HIRARC is divided into 3 stages which are hazard identification, risk assessment, and risk control. Hazard identification is performed based on interviews with the workers, the observations in the factory, and the historical data of accidents at PT. X. The result of the risk assessment shows 34% of activities is categorized as low risk, 58% of activities is categorized as moderate risk , 8% of activities is categorized as high risk and there is no activity in the category of extreme risk. Risk control will be performed on activities with moderate risk and high risk category. Based on the result, there are 4 potential hazards with high risk category, which are the sharpness of the material in the production area, shortness of breath due to workers are not wearing APD, shortness of breath due to the pungent smell from additives during the casting process, and the hook of the basket is fragile in the mixing process. Risk Control is undertaken by giving APD, safety sign, punishment, equipment maintenance, and make a special area for walking.